Free fatty acid-rich oils as potential benign organic solvent for dyes removal in solvent extraction system / Siti Fatimah Abdul Halim ... [et al.] - Abdul Halim, Siti Fatimah; Yusuf, Siti Aishah; Chang, Siu Hua; Amri, Nurulhuda (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
The extensive use of water in the textile industry results in the production of significant volumes of effluent-containing dyes, posing both economic and environmental concerns due to their harmful impact. Hence, the removal of dye from wastewater is very important for environmental protection and other aspects of well-being. Solvent extraction emerges as one of the promising methods used for dye removal. Nevertheless, the conventional organic phase formulation comprises an extractant, diluent, and modifier sourced from petroleumbased compounds, leading to environmental degradation. Thus, in this study, free fatty acid (FFA)-rich oils, i.e., Palm Kernel Fatty Acid Distillate (PKFAD) and Jatropha Oil (JO), were proposed as the green and benign organic solvent for the extraction of Crystal Violet-(CV) and Methylene Blue-(MB) from an aqueous solution. These FFA-rich oils act as reactive diluents due to the presence of FFA, which acts as an acidic extractant. Therefore, a new formulation of green sole-organic solvent without the addition of extractant and modifier was applied in this system. This study aimed to determine the best pH equilibrium for extracting CV and MB from different FFA-rich oils, i.e., PKFAD and JO. The results indicated the optimum extraction of CV is 95% at an equilibrium pH of 2.7 and 6.3 for PKFAD and JO, respectively. In comparison, the extraction of MB achieved 88% (pH 5.5) and 86% (pH 8.5) for PKFAD and JO, respectively. The stripping obtained a high removal percentage for both CV and MB, with 93% and 99%, respectively.